Avaliação da composição de especies de fungos micorrízicos arbusculares – FMA nos diferentes usos do solo na Amazônia Oriental - Martinez, Henry Alexander Reyes (2017)
As anthropic transformation of Amazonian rainforests into degraded lands continues, the role of arbuscular mycorrhizal fungi (AMF) remains in the dark. This paper describes changes in AMF (Glomerospore abundances, species composition and diversity and glomalin contents) along secondary forest succession, and we explore the impacts of seasonality and of soil physicochemistry. Research was conducted in a shifting cultivation region at the eastern periphery of Amazonia, in ‘young’ (3-4 yrs old) and ‘mid-aged’ (6-9 yrs old) secondary forest regrowth, and in mature (>120yrs old) rainforest, both in dry (November 2015) and in rainy (May 2016) seasons. We identify a total of 36 AMF species, corresponding to 24.1% of Brazil´s and 12.5% of the worldwide known AMF species richness. The genera Glomus and Acaulospora predominated in all successional stages, with 58.3% and 25% of all species richness respectively. BCA suggest that AMF species composition was driven mainly by seasonality (16%) and only marginally (though likewise significantly) by succession (8%). A subset of soil varieties (pH, OM, Al, CEC, Ca) had a high correlation (r2=0.46) with Glomerospore abundance and species composition. Though Glomerospore species diversidade did differ significantly between 3- 4 yrs-old and >120 yrs-old forests, differences were altogether small and – contrary to vegetation species diversity – diversity was highest in the 3-4 yrs-old regrowth. AMF floristic similarity between these contrasting vegetation types was high (‘r=0.79’),. Neither easily-extractable nor total glomalin contents differed significantly between seasons or successional stages, though they did contribute substantially (overall 2.5% average) to total soil organic matter carbon.. Our results support the view of a remarkably resilient limited set of AMF species with only very subtle differences between young (degraded) secondary regrowth and mature rainforests. Thus, the successional trajectories of vegetation recovery after repeated shifting cultivation cycles is likely not limited by AMF availability.